Pulp revascularization as an alternative to apexification therapies commonly applied to young teeth with incomplete roots (Research, Society and Development, 2022)
The dentist has some alternatives for inducing apical closure in cases in which the dental element presents with the root in formation. The use of techniques for apexification with MTA and calcium hydroxide have been suggested for years, and the prognosis when performing this therapy is very promising. On the other hand, teeth that have fragile walls and an inadequate crown-root ratio, even when apical closure is induced, have a dubious prognosis, since they do not have enough structure to withstand the intrinsic forces of mastication. Therefore, this study aimed to present a literature review on the revascularization technique, as well as to cite a survey of clinical cases that prove the effectiveness of this therapy for the treatment of young teeth that do not present complete root development. For this, searches were carried out on PubMed for studies published from 2020 to 2022 using the terms: pulp, revascularization, case and report. In view of the results seen, pulp revascularization is a good alternative to conventional apexification treatments, and should be performed mainly in cases where there is no adequate thickness and length of the root.